(untitled) (Homoeopathy for All, 2024)
Diseases which are transmitted from Human to human or animal to human are called miasmatic diseases. = acquired diseases. By “miasm” Hahnemann means an infectious principle, which, when taken into the organism, may set up a specific disease. According to Hahnemann, there were not only miasms of acute disease, like the infectious principle of scarlatina, for example, but also of chronic diseases. Among the latter he recognised three-syphilis, sycosis and psora.